Age-specific features of the absorptive and cytokine-inducing function of phagocytosis in children with recurrent acute respiratory infections - O.V. Tymoshyna; L.S. Ovcharenko; A.O. Vertehel; T.G. Andrienko; I.V. Samokhin; O.V. Kryazhev (Zaslavsky O.Yu., 2022)
Background. The study of the absorbing and cytokine-inducing function of phagocytosis is a mandatory starting point in assessing the state of anti-infective protection in children who suffer from frequent respiratory infections. It is important to understand and compare the features of phagocytosis in these children depending on their age. The purpose: to improve the diagnosis of immune disorders in children aged 2-5 and 6-10 years, who often suffer from acute respiratory diseases, by means of a comparative analysis of phagocytosis parameters and serum levels of some cytokines. Materials and methods. Under observation, there were 60 children aged 2 to 10 years who often suffer from acute infectious diseases of the respiratory tract. Two groups were formed: 1) children aged 2-5 years (n = 30); 2) children aged 6-10 years (n = 30). Results. Among patients of the first group compared to those of group 2, an increase in the frequency of low indicators of the phagocytic number (by 36.7 %, p < 0.05), phagocytic index (by 46.7 %, p < 0.05), the index of completion of phagocytosis (by 66.6 %, p < 0.05) and the staphylococcus-stimulated nitroblue tetrazolium test (by 46.4 %, p < 0.05), an increase in the frequency of high serum levels of interleukin-1β (by 33.3 %, p < 0.05), interleukin-10 (by 27.7 %, p < 0.05), a decrease in the frequency of high levels of interleukin-6 (by 16.7 %, p < 0.05). In the children of group 2 compared to those in the first one, high index of completion of phagocytosis was more often registered (by 70.0 %, p < 0.05), as well as more than a twofold increase in the ratio of interleukin-6/interleukin-10. Conclusions. In children aged 6-10 years, more frequent morbidity is due to a cytokine imbalance that was reflected in a more than a twofold increase in interleukin-6/interleukin-10 ratio, which is a negative factor indicating an enhancement of pro-inflammatory processes and a longer damage to the cells of the immune microenvironment.